Pemikiran Harun Nasution dan Relevansinya dengan Dunia Pendidikan Islam Kontemporer - Muhammad Rasyid Ridho; Maragustam Siregar (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2025)
This article critically analyzes Harun Nasution's thought and its relevance to contemporary Islamic education. Using a systematic literature review (SLR) approach, this study examines the contribution of Harun Nasution’s rational-religious concept, particularly in responding to the challenges of globalization, social change, and technological advancement in the modern era. The findings reveal that Harun Nasution emphasizes the integration of reason and revelation, the opening of ijtihad, and character strengthening as the foundation for Islamic educational reform. His educational model calls not only for eliminating the dichotomy between religious and general sciences, but also for fostering a dialogical, adaptive, and socially relevant learning system. Nevertheless, the implementation of these ideas still faces obstacles such as cultural resistance and limited understanding among educational practitioners. Overall, this article affirms that Harun Nasution's thought remains highly relevant and makes a significant contribution to the development of a progressive, integrative, and globally competitive Islamic education in the age of disruption.